The change of paradigms of national concepts in the work of Ján Kollár. Hungarism, Slavic reciprocity, Czechoslovakism, Illyrism - Kiss Szemán, Róbert (Bohemica Olomucensia, 2019)
Kollár as a poet and writer determined the political thinking in Central Europe. The diversity of genres of his oeuvre allows an in-depth investigation of this phenomenon. The study based on postmodernist cultural concepts focuses on the problem of the language code and latent elements in that part of Kollár's work which deals with the issue of Central European politics, cultures and nations.
Keywords: Central European culture of the Enlightenment; Hungarism; Panslavism; cultural mutuality of Slavic nations; Czechoslovakism; Illyrism